Description of Students Critical Thinking Ability in Temperature and Calor Material - Darmaji Darmaji; Dwi Agus Kurniawan; Astalini Astalini; Retno Wulan Dari (STKIP Singkawang, 2021)
The purpose of this study was to describe the critical thinking skills of students of SMAN 8 Muaro Jambi in physics learning material temperature and heat. The approach used in this study is a mixed-methods approach with a sequential explanatory design that combines sequential quantitative and qualitative research methods. The sample used in this study was 96 students of SMAN 8 Muaro Jambi. Data collection techniques using tests and interviews. The results showed that for the mastery of critical thinking skills as a whole on the material, the temperature and heat of the students were at a non-critical level with a percentage of 40.5%. Based on the results of the study, it was found that students of SMAN 8 Muaro Jambi were in the non-critical category. The low ability of students to think critically is because students are not used to being presented with active learning that maximizes their thinking potential. By doing this research, the teacher can improve students' critical thinking skills in learning physics, especially temperature and heat material.